A Case Report of Primary Extranodal Non-hodgkin Lymphoma First Presentation as a Soft Tissue Swelling Around the Wrist - Sopu, Alexandra (J Orthop Case Rep, 2015)
INTRODUCTION: Primary musculoskeletal extranodal non-Hodgkin lymphoma is a rare presentation and account for 5% of all primary extranodal non-Hodgkin lymphomas. Treatment uses a combination of chemotherapy and radiotherapy with good prognosis in unifocal manifestation. We report an unusual case of primary musculoskeletal extranodal lymphoma presenting as a soft tissue swelling around the wrist. CASE REPORT: A 75 year old lady was referred to the Orthopaedic Outpatients Department with a painless, slowly growing mass on the dorsum of the right wrist. Clinical examination revealed a 6 X 9 cm round painless mass on the dorsum of the distal radius adherent to both the underlying structures and skin. MRI of the wrist showed a large mass causing extensive osteolysis of the distal radius and extending proximally with abnormal replacement of the marrow. The patient was brought to theatre for biopsy and subsequent histopathological examination confirmed a B-cell non-Hodgkin lymphoma. The patient was referred to the Haematology Service for further treatment and follow-up. She received chemotherapy and radiotherapy with satisfactory results. CONCLUSION: Lymphoma presenting as a soft tissue mass is relatively uncommon and can easily be confused with a wide variety of inflammatory conditions, more common neoplasias as well as infectious diseases (tuberculosis). Though rare, extranodal lymphoma should be regularly included in the differential diagnosis of mass lesions.